Political change and material culture in Middle to Late Bronze Age Canaan - Bechar, Shlomit (History, archaeology, and culture of the levant, 2022)
"Examines the relationship between politics and material culture during the transition from the Middle Bronze Age to the Late Bronze Age in the southern Levant by studying architectural and ceramic changes"--